Synovitis, Acne, Pustulosis, Hyperostosis, and Osteitis Syndrome with Purely Osteolytic, Not Osteosclerotic, Lesions Mimicking a Malignant Tumor - Hideyuki Kinoshita; Takeshi Ishii; Hiroto Kamoda; Yoko Hagiwara; Toshinori Tsukanishi; Sumihisa Orita; Kazuhide Inage; Naoya Hirosawa; Seiji Ohtori; Tsukasa Yonemoto (Case Reports in Rheumatology)
Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a rare inflammatory disorder with multiple phenotypes. The syndrome has identifiable radiologic characteristics that are the most important when making a diagnosis. X-rays of cases diagnosed with SAPHO syndrome reveal sclerotic lesions or mixed lytic and sclerotic lesions. Pure osteolytic lesions in SAPHO syndrome are rare, and to the best of our knowledge, no study has reported the radiologic change of purely osteolytic lesions to osteosclerotic lesions over time. Herein, we report on the case of a woman experiencing severe left thigh acute pain and having a medical history of palmoplantar pustulosis. Although SAPHO syndrome was suspected because of palmoplantar pustulosis, based on radiologic findings, bone metastasis of a malignant tumor or chronic bacterial osteomyelitis owing to a purely osteolytic lesion was suspected. However, needle biopsy revealed no malignancy and bacterial culture was negative, thus suggesting SAPHO syndrome. Nonsteroidal anti-inflammatory drugs, bisphosphonates, and corticosteroids were administered, which improved the left thigh pain. Furthermore, the radiologic change of osteolytic lesions to osteosclerotic lesions over time was confirmed, leading to the diagnosis of SAPHO syndrome. Our case demonstrates that knowledge of atypical radiologic findings is necessary to diagnose initial SAPHO syndrome.